PENERAPAN MODEL PEMBELAJARAN CUPS UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DAN MINAT BELAJAR SISWA - Diah Rahmawati; Rini Utami; Dewi Mardhiyana (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study is to improve the ability to understand mathematical concepts and students' interest in learning by applying the CUPs learning model. This research is a classroom action research (PTK) which consists of four stages, namely planning, implementing, observing and reflecting. Data collection techniques carried out in this study used questionnaires, written tests, observations and interviews. Data analysis used is descriptive quantitative and qualitative. This research was conducted in two cycles. The results showed that there was an increase in the percentage of KKM in the ability to understand students' mathematical concepts and the percentage of students' learning interest. In cycle one, the percentage of KKM students' ability to understand mathematical concepts was 52.38% and in cycle two was 85.71%. This was also accompanied by an increase in student learning interest, namely in the first cycle of 71.43% and in the second cycle of student interest in learning, namely 90.48%. Therefore it can be concluded that through the CUPs learning model the ability to understand mathematical concepts and students' learning interest can be improved